Volume 5A: 41st Mechanisms and Robotics Conference 2017
DOI: 10.1115/detc2017-67721
|View full text |Cite
|
Sign up to set email alerts
|

Design Process of High Dynamics Multi-Link Flexible Robot Manipulators

Abstract: This paper presents a design process based on an advanced flexible robots modeling tool associated with realistic actuators models and pre-defined control architecture. This process implements dedicated feasibility and performance indicators, which are used to evaluate a design and its sensitivity on the considered parameters. The proposed approach is illustrated with theoretical and experimental results obtained with the YAKA robot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Traditional control schemes, such as standard PID (proportional-integral-derivative) regulators widely used in industrial controllers, have been demonstrated to be unsatisfactory to ensure effective compensation of unwanted elastic deformations. Therefore, attention should be paid to the synthesis of either optimal command generation techniques [2][3][4] or active vibration control schemes [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional control schemes, such as standard PID (proportional-integral-derivative) regulators widely used in industrial controllers, have been demonstrated to be unsatisfactory to ensure effective compensation of unwanted elastic deformations. Therefore, attention should be paid to the synthesis of either optimal command generation techniques [2][3][4] or active vibration control schemes [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%